Pengujian secara In Vitro Oligosakarida dari Ekstrak Tepung Buah Rumbia (Metroxylon sago Rottb.) sebagai Sumber Prebiotik - Muhammad Daud; Wiranda G Piliang; Komang G Wiryawan; Agus Setiyono (Agricultural Faculty, 2009)
In vitro analysis of oligosaccharide from extract rumbia fruit (Metroxylon sago Rottb.) as prebioticABSTRACT. Despite a range of commercially available oligosaccharides there is plenty of room to develop new, functionally enhanced prebiotics. current generation of oligosaccharides was not rationally developed. better understanding of factors determining the prebiotic activity of a particular oligosaccharide. Despite the range of commercially available oligosaccharides mixtures (mainly fructo and galacto-oligosaccharides), very few studies are focused on the mechanisms behind the prebiotic activity of particular oligosaccharides. Probably this lack is due to the unavailability of well characterized oligosaccharide fractions for prebiotic function assessment. The objectives of this research were to asses the ability of lactic acid bacteria in fermentation of oligosaccharide and as prebiotic (in vitro). Material used was oligosaccharide of purified rumbia fruit extract. Analysis of oligosaccharide as prebiotic was conducted in vitro using lactic acid bacteria. The lactic acid bacteria consisted Bifidobacterium bifidum, Bifidobacterium animalis, Lactobacillus bulgaricus and Lactobacillus casei Rhamnosus. The growth media for bacteria was a liquid MRS basic medium where glucose was substituted by oligosaccharide of purified rumbia fruit extract. Incubation was in aerob for Lactobacillus and anaerob for Bifidobacterium in incubator 37oC. The lactic acid bacteria was calculated 24-48 hours during incubation periode. The variables observed were: oligosaccharide component, ability of lactic acid bacteria in fermentation of oligosaccharide, and growth of lactic acid bacteria (Lactobacillus and Bifidobacterium). The result showed that the oligosaccharide component from extract rumbia fruit consisted of: sucrose, stacchiose, and raffinose. The result showed that the oligosaccharide extract rumbia fruit was significantly (P0.05) the growth of lactic acid bacteria (Lactobacillus and Bifidobacterium) and fermentation of oligosaccharide. It is concluded that oligosaccharide of rumbia fruit extract could be used as prebiotic.